2021
DOI: 10.1037/xhp0000889
|View full text |Cite
|
Sign up to set email alerts
|

Single-session label training alters neural competition between objects and faces.

Abstract: The extent to which visuocortical processing is altered when observers learn to categorize novel visual stimuli via labeling is not well understood. The present investigation used steady state visual evoked potential (ssVEP) frequency tagging to test the hypothesis that learning to categorize novel objects via labeling prompts a competitive advantage over concurrently presented stimuli. In the learning (label-training) phase, participants (n = 24) categorized objects according to two different species labels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 62 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Example data from one adult ( Silva et al, 2021 ) and one infant (Barry-Anwar et al, in preparation) are provided on the Open Science Framework companion site of this paper. Both data sets have undergone initial segmenting, filtering, and artifact control.…”
Section: Analyzing Frequency Tagging Data: a Step-by-step Demonstrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Example data from one adult ( Silva et al, 2021 ) and one infant (Barry-Anwar et al, in preparation) are provided on the Open Science Framework companion site of this paper. Both data sets have undergone initial segmenting, filtering, and artifact control.…”
Section: Analyzing Frequency Tagging Data: a Step-by-step Demonstrationmentioning
confidence: 99%
“…The first example data set data comes from a study with adult observers ( Silva et al, 2021 ). The full data set for this study can be found at: https://osf.io/a53s9/?view_only=1966f70fac954bac886381f908c7a275 .…”
Section: Analyzing Frequency Tagging Data: a Step-by-step Demonstrationmentioning
confidence: 99%
See 2 more Smart Citations